Social justice and growth : the role of the minimum wage. (International journal of labour research ;, 2012)
This issue of the International Journal of Labour Research is wholly dedicated to the question of the minimum wage, a matter that has gained in importance and profile in recent years. No doubt, the main reasons behind this rise in prominence relate to the stagnation of wages in several parts of the world, a generalized increase in earnings inequality as well as the rise in social unrest across the globe.